Influence of PEEK Coating on Hip Implant Stress Shielding: A Finite Element Analysis. (14th March 2016) - Anguiano-Sanchez, Jesica; Martinez-Romero, Oscar; Siller, Hector R.; Diaz-Elizondo, Jose A.; Flores-Villalba, Eduardo; Rodriguez, Ciro A.
Abstract : Stress shielding is a well-known failure factor in hip implants. This work proposes a design concept for hip implants, using a combination of metallic stem with a polymer coating (polyether ether ketone (PEEK)). The proposed design concept is simulated using titanium alloy stems and PEEK coatings with thicknesses varying from 100 to 400 μ m. The Finite Element analysis of the cancellous bone surrounding the implant shows promising results. The effective von Mises stress increases between 81 and 92% for the complete volume of cancellous bone. When focusing on the proximal zone of the implant, the increased stress transmission to the cancellous bone reaches between 47 and 60%. This increment in load transferred to the bone can influence mineral bone loss due to stress shielding, minimizing such effect, and thus prolonging implant lifespan.